2022
DOI: 10.1155/2022/9282484
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of SIRT2 in Regulating Physiological and Pathological Signal Transduction

Abstract: Sirtuin 2 (SIRT2), as a member of the sirtuin family, has representative features of evolutionarily highly conserved nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase activity. In addition, SIRT2, as the only sirtuin protein colocalized with tubulin in the cytoplasm, has its own functions and characteristics. In recent years, studies have increasingly shown that SIRT2 can participate in the regulation of gene expression and regulate signal transduction in the metabolic pathway mainly through its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 163 publications
0
13
0
Order By: Relevance
“…AXIN1, for example, a regulator molecule of the Wnt signaling pathways [ 75 ], has been shown to correlate with disease severity in endometriosis [ 76 ]. SIRT2 has a wide range of regulatory functions ranging from neuronal to immunological and metabolic homeostasis [ 77 , 78 ]. Our study, together with other protein disease signature (PDS) studies, shows the importance of analyzing multiple inflammatory markers and comorbidities to explore a more complete picture of a disease.…”
Section: Discussionmentioning
confidence: 99%
“…AXIN1, for example, a regulator molecule of the Wnt signaling pathways [ 75 ], has been shown to correlate with disease severity in endometriosis [ 76 ]. SIRT2 has a wide range of regulatory functions ranging from neuronal to immunological and metabolic homeostasis [ 77 , 78 ]. Our study, together with other protein disease signature (PDS) studies, shows the importance of analyzing multiple inflammatory markers and comorbidities to explore a more complete picture of a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al showed that SIRT2 decreased the acetylation of PEPCK1 and the association between PEPCK1 and UBR5, increased the stability of PEPCK1, and promoted gluconeogenesis [ 201 ]. It has also been shown that SIRT2 inhibition not only increased the stability of GKRP protein and promoted the degradation of ALDOA but also inhibited glucose-stimulated insulin secretion and reduced glycolytic flux by regulating the Akt/GSK3β/β-linked protein pathway in β-cells [ 202 ].…”
Section: Sirtuins As a Novel Drug Target For Type 2 Diabetesmentioning
confidence: 99%
“…Consequently, dysregulation of SIRT2 has been associated with a broad spectrum of diseases including metabolic and neurological disorders, cancer, and aging [ 51 , 52 ]. By forming a crosstalk between gene expression regulation and metabolic pathways, SIRT2 is involved in all aspects of cell metabolism, including lipogenesis, fatty acid oxidation, gluconeogenesis, and glycolysis [ 53 ]. SIRT2 promotes gluconeogenesis by deacetylating FOXO1 and Phosphoenolpyruvate Carboxykinase (PEPCK), enhances glycolysis by interacting with glycolytic enzymes (ALDOA, PGK1, ENO1, GAPDH, PFKP, PKM, LDH) [ 54 , 55 ], and regulates insulin secretion through the PI3K/AKT pathway [ 56 ].…”
Section: Sirt Proteins: An Overview Of Structure and Functionmentioning
confidence: 99%